Shariaâ€™ and Criticism with TakhrÃ®j Method Concerning The Hadith of Marriage Mut’ah Futuh Makkah and Mut’ah Rasulullah Allowed While God Forgives - Tadjudin, Azi Ahmad (Proceeding International Conference on Islam and Civilization (ICONIC), 2021)
This study examines the importance of studying the science of hadith through explanation and criticism, both in terms of arguments and texts. The purpose of this study is to find out the hadith "Enjoyment in the era of the conquest of Makkah", a history and knowledge in terms of the value and quantity of all hadiths and their validity in concluding laws. As for the research method in this study, we took the following scientific path, including Examination of the texts we found from well-known hadith books, then elements of hadith in terms of links and texts, then the distribution of hadith, then correction of hadith and its application, then the vocabulary and the purpose of the meaning of the hadith, then the causes of its occurrence and appropriateness, then summing up the law and its wisdom, then the problem and understanding, and the other is a summary and its consequences. The results of this study indicate that Mut’ah was allowed twice and forbidden twice, allowed before the Battle of Khaybar and forbidden after it, then allowed before the conquest of Mecca and forbidden after three days forever. We take advantage of this study, which means studying graduation by way of explanation and criticism, as the basis for developing Islamic sciences in dealing with the problems of the life of the Islamic nation in our present and future era.